Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery using same

By using a combination of silicon and carbon active materials with a specific particle size distribution in lithium-ion secondary batteries, combined with binders and conductive additives, the problem of expansion and contraction of negative electrode active materials is solved, the energy density and life of the battery are improved, and fast charging and discharging performance is achieved.

CN120693701APending Publication Date: 2025-09-23ENVISION AESC JAPAN LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380094312.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2023-12-15
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

In existing lithium-ion secondary batteries, when graphite is used as the negative electrode active material, it is difficult to effectively suppress the expansion and contraction of the negative electrode active material during charge and discharge, resulting in a shortened battery life.

Method used

A negative electrode active material layer containing silicon-based active material SiOx and carbon-based active material is used. By controlling the particle size distribution, the D10max/D10min and D90max/D90min ratios of the silicon-based active material are ensured to be within a specific range. Combined with a binder and a conductive additive, a high-density and stable negative electrode active material layer is formed.

Benefits of technology

It effectively inhibits the expansion of the negative electrode active material, improves the energy density and life of the battery, and achieves fast charge and discharge performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The purpose of the present invention is to suppress expansion and contraction of a negative electrode active material layer during charging and discharging of a non-aqueous electrolyte secondary battery including a lithium ion secondary battery when a Si-based negative electrode active material is used, increase the life (cycle characteristics) of the non-aqueous electrolyte secondary battery, and improve fast charging properties. The negative electrode active material includes: a silicon-based active material (A) including SiOx (wherein x is a number satisfying 0.5 < = x < = 1.6); a carbon-based active material (B) containing secondary particles formed by aggregating the primary particles; and a carbon-based active material (C) including primary particles in which secondary particles are not formed, in which D10A is 3 [mu] m or more, the value of D10max / D10min is 2.5 or less when the maximum value of D10 among the values of D10A, D10B, and D10C is D10max and the minimum value is D10min, and the value of D90max / D90min is 2.0 or less when the maximum value of D90 among the values of D90A, D90B, and D90C is D90max and the minimum value is D90min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery using the negative electrode. Background Art

[0002] In addition to being put into practical use as batteries for automobiles including hybrid vehicles and electric vehicles, non-aqueous electrolyte secondary batteries are also used as batteries for small electronic devices including mobile terminals. As such batteries, lithium-ion secondary batteries are particularly widely used. Lithium-ion secondary batteries are required to have various characteristics such as output characteristics, energy density, capacity, life, and high-temperature stability. In particular, in order to miniaturize the battery, improving the volume energy density and high capacity of the battery have become urgent issues. In particular, for lithium-ion secondary batteries for electric vehicles, it is required to increase the energy density in order to further extend the cruising range. Therefore, various improvements have been made to the battery structure including electrodes or electrolytes.

[0003] Graphite is known to be used as a negative electrode active material for lithium-ion secondary batteries. Graphite is inexpensive, exhibits minimal degradation due to the battery's charge and discharge cycles, and is highly safe, leading to its widespread use. However, in existing lithium-ion secondary batteries using graphite materials as negative electrode active materials, further increases in energy density are difficult to achieve, leading to the search for higher-capacity negative electrode active materials. Silicon-based negative electrode active materials containing silicon or silicon oxide (hereinafter sometimes referred to as "Si-based negative electrode active materials," "Si-based negative electrode active materials," etc.) are attracting attention as high-capacity negative electrode active materials.

[0004] For example, Patent Document 1 discloses a negative electrode that specifies the ratio of the cumulative particle diameters D90 to D10 of the entire carbonaceous particles and silicon oxide particles in order to provide a non-aqueous secondary battery with excellent charge and discharge efficiency.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2018 / 097212 Summary of the Invention

[0008] Problems to be solved by the invention

[0009] Patent Document 1 discloses that the average particle size (particle size at the 50% cumulative portion from the small particles) (d50) is 3 μm or more and 30 μm or less, the particle size at the 10% cumulative portion from the small particles (d10) is 0.1 μm or more and 10 μm or less, the ratio of the particle size at the 90% cumulative portion from the small particles (d90) to d10 (R1 = d90 / d10) is 3 or more and 20 or less, and the ratio of d50 to d10 (R2 = d50 / d10) is 1.7 or more and 5 or less. However, under these conditions, the loss of contact between active material particles caused by repeated expansion and contraction of the negative electrode during charge and discharge of lithium-ion secondary batteries cannot be sufficiently suppressed.

[0010] The present invention aims to suppress the expansion and contraction of the negative electrode active material during charge and discharge of a non-aqueous electrolyte secondary battery including a lithium ion secondary battery when using a Si-based negative electrode active material, thereby improving the life (cycle characteristics) of the non-aqueous electrolyte secondary battery.

[0011] Technical means to solve the problem

[0012] One embodiment of the present invention is a negative electrode for a non-aqueous electrolyte secondary battery comprising a negative electrode active material layer containing a negative electrode active material, a binder, and a conductive additive. The negative electrode active material is characterized by comprising: a silicon-based active material (A) containing SiO x (where x is a number that satisfies 0.5≦x≦1.6);

[0013] A carbon-based active material (B) comprising secondary particles formed by agglomeration of primary particles; and

[0014] The carbon-based active material (C) includes primary particles that do not form secondary particles,

[0015] In the volume-based cumulative particle size distribution of the negative electrode active material particles, the particle size at which the cumulative particle volume from the smaller particle size reaches x [%] of the total particle volume is expressed as Dx [μm],

[0016] D10 of the silicon-based active material (A) A 3 μm or more,

[0017] When the silicon-based active material (A) is added to D10 A 、D10 of the carbon-based active material (B) B , and D10 of the carbon-based active material (C) C The largest value of D10 is set as D10 max , set the minimum value to D10 min When D10 max / D10 min The value is below 2.5,

[0018] When the silicon-based active material (A) is A 、D90 of the carbon-based active material (B) B , and D90 of the carbon-based active material (C) C The largest D90 value among the values ​​is set as D90 max , set the minimum value to D90 min When D90 max / D90 min The value is 2.0 or less.

[0019] Effects of the Invention

[0020] The negative electrode for a nonaqueous electrolyte secondary battery of the present invention suppresses expansion and contraction even when a Si-based negative electrode active material is used, thereby providing a negative electrode for a nonaqueous electrolyte secondary battery excellent in rapid charge and discharge, and a nonaqueous electrolyte secondary battery using the negative electrode. DETAILED DESCRIPTION

[0021] The following describes an embodiment of the present invention. One embodiment is a negative electrode for a non-aqueous electrolyte secondary battery comprising a negative electrode active material layer including a negative electrode active material, a binder, and a conductive additive. The negative electrode active material is characterized by comprising: a silicon-based active material (A) comprising SiO x (where x is a number that satisfies 0.5≦x≦1.6);

[0022] A carbon-based active material (B) comprising secondary particles formed by agglomeration of primary particles; and

[0023] The carbon-based active material (C) includes primary particles that do not form secondary particles,

[0024] In the volume-based cumulative particle size distribution of the negative electrode active material particles, the particle size at which the cumulative particle volume from the smaller particle size reaches x [%] of the total particle volume is expressed as Dx [μm],

[0025] D10 of the silicon-based active material (A) A 3 μm or more,

[0026] When the silicon-based active material (A) is added to D10 A 、D10 of the carbon-based active material (B) B , and D10 of the carbon-based active material (C) C The largest value of D10 is set as D10 max , set the minimum value to D10 min When D10 max / D10 min The value is below 2.5,

[0027] When the silicon-based active material (A) is A 、D90 of the carbon-based active material (B) B , and D90 of the carbon-based active material (C) C The largest D90 value among the values ​​is set as D90 max , set the minimum value to D90 min When D90 max / D90 min The value is 2.0 or less.

[0028] In an embodiment, the so-called non-aqueous electrolyte secondary battery is a battery that mainly uses an organic solvent-based electrolyte and can be repeatedly charged and discharged. As a non-aqueous electrolyte secondary battery, a lithium-ion secondary battery can be cited. The non-aqueous electrolyte secondary battery includes a non-aqueous electrolyte secondary battery negative electrode as its constituent component. In an embodiment, the so-called negative electrode is a thin plate or sheet-shaped battery component in which a negative electrode active material layer is formed by coating or rolling a mixture containing a negative electrode active material on a negative electrode current collector such as a metal foil such as copper foil and drying it. That is, the negative electrode includes a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material coated on both sides thereof. In an embodiment, the negative electrode active material layer preferably includes a negative electrode active material, a binder and a conductive additive. The so-called negative electrode active material is a substance used for the negative electrode among substances that participate in the reaction of generating electric energy. In addition, the so-called binder is generally a substance used to bind the negative electrode active material particles so that the negative electrode active material particles are in electrical contact with each other. The so-called conductive additive is a material used to reduce the resistance of the electrode.

[0029] In an embodiment, the negative electrode active material includes SiO x (where x is a number satisfying 0.5≦x≦1.6) and a carbon-based active material. Here, the silicon-based active material (A) is a chemical formula SiO x Silicon oxide, where x is a number satisfying 0.5≦x≦1.6. The silicon-based active material (A) may be a single compound or a mixture of multiple compounds. The silicon-based active material is preferably in the form of particles having approximately uniform or inconsistent sizes. The negative electrode active material may also contain a lithium silicon compound. The lithium silicon compound has the chemical formula Li 4.4 Si, Li 3.75Si, or a compound containing lithium and silicon, such as Li4SiO4 (lithium silicate). Lithium-silicon compounds are stable compounds that do not release lithium during charge and discharge of non-aqueous electrolyte secondary batteries. Therefore, by using them in conjunction with silicon-based active materials, which are prone to volume changes during charge and discharge of non-aqueous electrolyte secondary batteries, the volume change of the negative electrode active material layer can be suppressed. Furthermore, the silicon-based active material (A) can also be pre-doped with lithium. In the presence of a lithium-silicon compound or lithium-doped silicon, the particle size of the silicon-based active material (A), unless otherwise specified, refers to the particle size of the entire silicon-containing compound.

[0030] In this specification, in the volume-based cumulative particle size distribution of the negative electrode active material particles, the particle size at which the cumulative particle volume from the smaller particle size reaches x [%] of the total particle volume is expressed as Dx [μm]. A Preferably, the D50 of the silicon-based active material (A) is 3 μm or more. A Preferably, the thickness is 7 μm or more and 13 μm. Furthermore, lithium can be pre-doped into the silicon-based active material. Here, the so-called D50 A , refers to the average particle size of the silicon-based active material (A).

[0031] The negative electrode active material also includes a carbon-based active material. The carbon-based active material is preferably natural graphite, artificial graphite, hard carbon, soft carbon or any mixture thereof. Here, the so-called graphite is a carbon material of hexagonal plate-like crystals of the hexagonal system, sometimes referred to as graphite, graphite, etc. Natural graphite and artificial graphite include natural graphite with a coating based on amorphous carbon, and artificial graphite with a coating based on amorphous carbon. Here, the so-called amorphous carbon is a carbon material that may have a structure similar to graphite in part and a structure in which microcrystals randomly form a network, and is amorphous as a whole. Examples of amorphous carbon include carbon black, coke, activated carbon, carbon fiber, hard carbon, soft carbon, mesoporous carbon, etc. When artificial graphite is used, the interlayer distance d value (d 002 ) is 0.33 nm or more. The crystal structure of artificial graphite is generally thinner than that of natural graphite. When artificial graphite is used as a negative electrode active material for non-aqueous electrolyte secondary batteries, especially lithium ion secondary batteries, it is necessary to have an interlayer distance that allows lithium ions to be inserted. The interlayer distance that allows lithium ions to be inserted / deleted can be measured using the d value (d 002) It is estimated that if the d value is 0.33 nm or more, the insertion / desorption of lithium ions can be carried out without problems. In an embodiment, the carbon-based active material preferably contains at least two types. The two carbon-based active materials are respectively referred to as carbon-based active material (B) and carbon-based active material (C). The carbon-based active material (B) is preferably a carbon-based active material comprising secondary particles formed by the aggregation of primary particles. The carbon-based active material (B) is preferably artificial graphite whose surface is coated with amorphous carbon. In addition, the carbon-based active material (C) is a primary particle different from the primary particle of the carbon-based active material (B), and the primary particles do not aggregate and do not form secondary particles. The carbon-based active material (C) is preferably artificial graphite whose surface is not coated.

[0032] The content of the silicon-based active material relative to the total amount of the negative electrode active material in the negative electrode active material layer is particularly preferably greater than 5% by mass and less than 50% by mass. More preferably, the content of the silicon-based active material is greater than 10% by mass and less than 20% by mass. If the content of the silicon-based active material is too much, the volume change of the negative electrode active material during charge and discharge of the non-aqueous electrolyte secondary battery becomes larger and is not preferred. In addition, if the content of the silicon-based active material is too little, it is difficult to obtain the effect of high energy density.

[0033] In this embodiment, it is preferable that the silicon-based active material (A) is A 、D10 of carbon-based active material (B) B , and D10 of carbon-based active material (C) C The largest value of D10 is set as D10 max , set the minimum value to D10 min When D10 max / D10 min The value is less than 2.5.

[0034] More preferably, when the D90 of the silicon-based active material (A) is A 、D90 of carbon-based active material (B) B , and D90 of carbon-based active material (C) C The largest D90 value among the values ​​is set as D90 max , set the minimum value to D90 min When D90 max / D90 min The value of is 2.0 or less. By using a combination of negative electrode active materials having such a particle size distribution, the packing density of the negative electrode active material particles can be optimized, and the expansion and contraction of the negative electrode active material layer accompanying charge and discharge can be suppressed.

[0035] Regarding the formulation of the negative electrode active material, the content of the silicon-based active material (A) is particularly preferably greater than 5% by mass and less than 50% by mass relative to the total amount of the negative electrode active material in the negative electrode active material layer. More preferably, the content of the silicon-based active material (A) is greater than 10% by mass and less than 20% by mass. Excessive silicon-based active material (A) content increases the volume change of the negative electrode active material during charge and discharge of the non-aqueous electrolyte secondary battery, which is not preferred. Furthermore, if the content of the silicon-based active material (A) is too low, it is difficult to achieve the effect of increasing energy density.

[0036] The negative electrode active material can achieve good electrical contact by binding the particles to each other using a binder. The binder preferably comprises poly(meth)acrylic acid, a metal salt of poly(meth)acrylic acid, an alkyl ester of poly(meth)acrylic acid, or any mixture thereof. Compounds suitable as binders include, for example, polyacrylic acid, polymethacrylic acid; sodium polyacrylate, potassium polyacrylate, sodium polymethacrylate, potassium polymethacrylate; polyethyl acrylate, polyethyl acrylate, polybutyl acrylate, polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, or any mixture thereof. The content of the binder is preferably 2% by mass or more and less than 10% by mass relative to the total solid content of the negative electrode active material layer. If the content of the binder is too much, the portion of the active material surface covered by the binder increases, and thus the ion conductivity or electron conductivity may be reduced. In addition, if the content of the binder is too little, it may be impossible to properly establish electrical contact between the negative electrode active material particles.

[0037] As a binder component, it is particularly preferred to include, in addition to the aforementioned compounds, carboxymethyl cellulose (CMC), a cellulose derivative, or a metal salt of carboxymethyl cellulose (e.g., sodium carboxymethyl cellulose or potassium carboxymethyl cellulose). Carboxymethyl cellulose or the metal salt of carboxymethyl cellulose stabilizes the binder compound and also stabilizes the electrical contact of the negative electrode active material. When CMC or a metal salt of CMC is further added as a binder component, the content of CMC or its metal salt is preferably 0.05% to 1.5% by mass, particularly preferably 0.08% to 0.8% by mass, and even more preferably 0.15% to 0.30% by mass, relative to the total solids content of the negative electrode active material layer.

[0038] In an embodiment, the content of the silicon-based active material (A) is preferably 5% by mass or more and 50% by mass or less relative to the total solid content of the negative electrode active material layer, and the content of the binder is preferably 2% by mass or more and 8% by mass or less relative to the total solid content of the negative electrode active material layer.

[0039] More preferably, the content of the silicon-based active material (A) is 10% by mass or more and 20% by mass or less relative to the total solid content of the negative electrode active material layer, and the content of the binder is 2% by mass or more and 6% by mass or less relative to the total solid content of the negative electrode active material layer.

[0040] Furthermore, it is further preferred that the content of the silicon-based active material (A) is 15% by mass or more and 20% by mass or less relative to the total solid content of the negative electrode active material layer, and the content of the binder is 2.5% by mass or more and 3.8% by mass or less relative to the total solid content of the negative electrode active material layer.

[0041] By appropriately adjusting the contents of the silicon-based active material (A) and the binder, the energy density of the non-aqueous electrolyte secondary battery can be increased.

[0042] The negative electrode active material layer preferably further contains a conductive additive. A conductive additive is a material used to reduce the resistance of the electrode. Examples of conductive additives include carbon materials such as carbon nanofibers, carbon black such as acetylene black and Ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, and carbon nanotubes. In embodiments, carbon nanotubes (CNTs) are particularly preferred as the conductive additive. CNTs are materials with a coaxial tube structure consisting of a six-membered ring network of carbon atoms (graphene) in a single or multi-layer structure. They include single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). While any type of CNT can be used, it is preferred to use aggregated SWCNTs, where the SWCNTs are aggregated to form a longer, more elongated shape than a single SWCNT. This prevents the conductive network in the negative electrode from breaking when the negative electrode active material layer expands or contracts. SWCNTs are preferably pre-dispersed in a solvent and mixed with at least one of the silicon-based active material (A), carbon-based active material (B), and carbon-based active material (C). The SWCNTs are then attached to the surface of the at least one active material, and the elongated SWCNTs are positioned between at least two of the silicon-based active material (A), carbon-based active material (B), and carbon-based active material (C). Furthermore, carbon black may be used separately from the SWCNTs to enhance conductivity in the negative electrode active material layer.

[0043] When CNTs are used as the conductive additive, the CNT content is preferably 0.01% by mass to 1% by mass, particularly preferably 0.03% by mass to 0.8% by mass, and further preferably 0.1% by mass to 0.5% by mass, relative to the total solid content of the negative electrode active material layer.

[0044] Furthermore, electrode additives commonly used for forming electrodes, such as a thickener, a dispersant, and a stabilizer, may be appropriately used in the negative electrode active material layer.

[0045] The negative electrode active material of the embodiment can form a high-density negative electrode active material layer by having uniform distribution of fine powder, and can also prevent local variations in expansion and contraction of the negative electrode active material layer, thereby improving the cycle characteristics of the non-aqueous electrolyte secondary battery.

[0046] Another embodiment of the present invention is a nonaqueous electrolyte secondary battery including at least the negative electrode for a nonaqueous electrolyte secondary battery according to one embodiment, a positive electrode for a nonaqueous electrolyte secondary battery, a separator, and a nonaqueous electrolyte.

[0047] The nonaqueous electrolyte secondary battery of the embodiment includes at least a negative electrode for a nonaqueous electrolyte secondary battery, a positive electrode for a nonaqueous electrolyte secondary battery, a separator, and a nonaqueous electrolyte as its constituent members.

[0048] In an embodiment, the positive electrode is a thin plate or sheet-like battery component formed by coating or rolling a mixture containing a positive electrode active material on a positive electrode current collector such as a metal foil such as aluminum foil and drying it to form a positive electrode active material layer. That is, the positive electrode includes a positive electrode current collector and a positive electrode active material layer containing a positive electrode active material coated on both sides or one side thereof. In an embodiment, the positive electrode active material layer preferably includes a positive electrode active material and a binder. The so-called positive electrode active material is a substance used for the positive electrode among substances that participate in the reaction of generating electric energy. In addition, the so-called binder is generally a substance used to bind the positive electrode active material particles in order to make the positive electrode active material particles electrically contact each other.

[0049] The positive electrode active material used in the embodiment preferably contains a lithium-nickel composite oxide as the positive electrode active material. The so-called lithium-nickel composite oxide is a general formula Li x Ni y Me (1-y)A transition metal composite oxide containing lithium and nickel represented by O2 (herein, Me is at least one metal selected from the group consisting of Al, Mn, Na, Fe, Co, Cr, Cu, Zn, Ca, K, Mg and Pb). Particularly preferably, it comprises a lithium-manganese composite oxide. Examples of lithium-manganese composite oxides include lithium manganate (LiMnO2) with a zigzag layer structure and spinel lithium manganate (LiMn2O4). In addition, the positive electrode active material particularly comprises a general formula Li x Ni y Co z Mn (1-y-z) A lithium nickel manganese cobalt composite oxide having a layered crystal structure represented by O2. Here, x in the general formula is 1≦x≦1.2, y and z are positive numbers satisfying y+z<1, and the value of y is greater than 0.5. In addition, if the proportion of manganese becomes large, it is difficult to synthesize a single-phase composite oxide, so it is ideal to set it to 1-yz≦0.4. In order to obtain a high-capacity battery, it is particularly preferred to set it to y>1-yz, y>z. The lithium-nickel composite oxide having the general formula is lithium-nickel-cobalt-manganese composite oxide (Lithium Nickel Cobalt Manganese Oxide) (hereinafter sometimes referred to as "NCM"). NCM is a lithium-nickel composite oxide suitable for achieving high-capacity batteries.

[0050] Examples of the binder that forms the positive electrode active material layer together with the positive electrode active material include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF); conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile butadiene rubber (NBR); and polysaccharides such as carboxymethyl cellulose (CMC), xanthan gum, guar gum, and pectin.

[0051] The positive electrode active material layer may also contain a conductive additive, if necessary. Examples of conductive additives include carbon materials such as carbon nanofibers, carbon black such as acetylene black and Ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, and carbon nanotubes. In embodiments, carbon nanotubes (CNTs) are particularly preferred as the conductive additive. CNTs are materials with a coaxial tube structure consisting of a six-membered ring network of carbon atoms (graphene) in the form of single or multiple layers. They include single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). While any type of CNT can be used, it is preferred to use aggregated SWCNTs, where the SWCNTs are aggregated to form a longer, more elongated shape than a single SWCNT. This prevents the conductive network in the positive electrode from breaking when the positive electrode active material layer expands or contracts. Furthermore, to enhance conductivity in the positive electrode active material layer, carbon black may be used separately from the SWCNTs. Furthermore, electrode additives generally used for forming electrodes, such as a thickener, a dispersant, and a stabilizer, may be appropriately used in the positive electrode active material layer.

[0052] The non-aqueous electrolyte secondary battery of the embodiment includes a separator as a component. For example, a polyolefin film can be used as the separator. The so-called polyolefin is a compound obtained by polymerizing or copolymerizing α-olefins such as ethylene, propylene, butene, pentene, and hexene. For example, in addition to polyethylene, polypropylene, polybutene, polypentene, and polyhexene, their copolymers can also be mentioned. When a polyolefin film is used as a separator, a structure having pores that are blocked when the battery temperature rises, that is, a porous or microporous polyolefin film is suitable. By having such a structure of the polyolefin film, even if the battery temperature rises, the separator will be blocked (closed), thereby interrupting the ion flow. That is, the uniaxially stretched polyolefin film shrinks when the battery is heated, and the pores are blocked, thereby preventing a short circuit between the positive and negative electrodes. In order to exert the shutdown effect, it is very preferable to use a porous polyethylene film.

[0053] Alternatively, cross-linked membranes can be used as separators. Porous or microporous polyolefin membranes shrink when heated, so when the battery overheats, the membrane shrinks and closes. However, if the membrane's thermal shrinkage is too large, the membrane's area will change significantly, potentially allowing large currents to flow. Cross-linked polyolefin membranes have an appropriate thermal shrinkage, so even when overheated, they can shrink enough to block the pores without significantly changing their area.

[0054] The separator used in the embodiments may also have a heat-resistant microparticle layer on one or both sides of the separator. In this case, the heat-resistant microparticle layer, provided to prevent overheating of the battery, comprises inorganic microparticles that have a heat resistance temperature of 150°C or higher and are stable during electrochemical reactions. Examples of such inorganic microparticles include inorganic oxides such as silica, alumina (α-alumina, β-alumina, θ-alumina), iron oxide, titanium oxide, barium titanate, and zirconium oxide; and minerals such as boehmite, zeolite, apatite, kaolin, spinel, mica, and mullite.

[0055] The non-aqueous electrolyte secondary battery of the embodiment includes a non-aqueous electrolyte. The non-aqueous electrolyte is an electrically conductive substance formed by dissolving an ionic substance in an organic solvent. The negative electrode for the non-aqueous electrolyte secondary battery is overlapped with the positive electrode for the non-aqueous electrolyte secondary battery, and a separator is arranged between them. The non-aqueous electrolyte secondary battery element including the negative electrode and the non-aqueous electrolyte is a unit of the main components of the non-aqueous electrolyte secondary battery. Typically, a stack formed by overlapping a plurality of negative electrodes for non-aqueous electrolyte secondary batteries and a plurality of positive electrodes for non-aqueous electrolyte secondary batteries with a plurality of separators is immersed in a non-aqueous electrolyte. The non-aqueous electrolyte that can be used in the embodiments is primarily a non-aqueous electrolyte solution, preferably comprising a mixture of chain carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), di-n-propyl carbonate, di-tert-propyl carbonate, di-n-butyl carbonate, di-isobutyl carbonate, or di-tert-butyl carbonate, and cyclic carbonates such as propylene carbonate (PC) and ethylene carbonate (EC). The non-aqueous electrolyte solution is prepared by dissolving a lithium salt such as lithium hexafluorophosphate (LiPF6), lithium fluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), or lithium perchlorate (LiClO4) in this carbonate mixture.

[0056] The non-aqueous electrolyte may also contain a cyclic carbonate compound other than the cyclic carbonate as an additive. Examples of cyclic carbonates used as additives include vinylene carbonate (VC). Halogen-containing cyclic carbonate compounds may also be used as additives. These cyclic carbonates also form protective coatings on the negative and positive electrodes of non-aqueous electrolyte secondary batteries during the charge and discharge processes of the non-aqueous electrolyte secondary battery. In particular, these compounds can prevent sulfur-containing compounds such as the disulfonic acid compound or disulfonic acid ester compound from attacking the positive electrode active material containing the lithium-nickel composite oxide. Examples of halogen-containing cyclic carbonate compounds include fluoroethylene carbonate (FEC), difluoroethylene carbonate, trifluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, and trichloroethylene carbonate. Fluoroethylene carbonate, a cyclic carbonate compound containing both a halogen and an unsaturated bond, is particularly preferably used.

[0057] In addition, the non-aqueous electrolyte may also contain a disulfonic acid compound as an additive. A disulfonic acid compound is a compound having two sulfonic groups in one molecule, including a disulfonate compound in which the sulfonic groups form a salt with a metal ion, or a disulfonate compound in which the sulfonic groups form an ester. One or both of the sulfonic groups in the disulfonic acid compound may form a salt with a metal ion, or may be in the form of an anion. Examples of disulfonic acid compounds include methanedisulfonic acid, 1,2-ethanedisulfonic acid, 1,3-propanedisulfonic acid, 1,4-butanedisulfonic acid, benzenedisulfonic acid, naphthalenedisulfonic acid, biphenyldisulfonic acid, and their salts (lithium methanedisulfonate, lithium 1,2-ethanedisulfonate, etc.), and their anions (methanedisulfonate anion, 1,2-ethanedisulfonate anion, etc.). Examples of the disulfonic acid compound include disulfonate compounds, including chain disulfonates such as alkyl diesters or aryl diesters of methanedisulfonic acid, 1,2-ethanedisulfonic acid, 1,3-propanedisulfonic acid, 1,4-butanedisulfonic acid, benzenedisulfonic acid, naphthalenedisulfonic acid, or biphenyldisulfonic acid; and cyclic disulfonates such as methylene methanedisulfonate, ethylene methanedisulfonate, and propylene methanedisulfonate.

[0058] The non-aqueous electrolyte secondary battery of the embodiment is usually sealed by an outer packaging. The so-called sealing refers to that at least a portion of the non-aqueous electrolyte secondary battery element is surrounded by the outer packaging material so as not to be exposed to the outside air. The outer packaging of the non-aqueous electrolyte secondary battery is a frame with gas barrier properties and capable of sealing the non-aqueous electrolyte secondary battery element, or a bag-shaped component containing a soft material. The outer packaging can be suitably an aluminum can, or an aluminum laminated sheet formed by stacking aluminum foil and polypropylene, etc. That is, with respect to the outer packaging, any material can be used as long as it is a material that prevents the non-aqueous electrolyte from seeping out to the outside. The outer packaging may be made of a laminated film having a heat-resistant protective layer such as polyester, polyamide, or liquid crystal polymer as the outermost layer, and a sealant layer comprising a thermoplastic resin as the innermost layer. The thermoplastic resins include polyethylene, polypropylene, ionomers, acid-modified polyethylenes such as maleic acid-modified polyethylene, acid-modified polypropylenes such as maleic acid-modified polypropylene, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyethylene isophthalate (PEI), blends of PET and PEN, blends of PET and PEI, polyamide resins, blends of polyamide resins and PET, and blends of xylylene-containing polyamides and PET. The outer packaging may also be formed by combining one or more of these laminated films, bonding or welding them together, and then forming multiple layers. Aluminum, tin, copper, nickel, or stainless steel may be used as the gas barrier metal layer. The thickness of the metal layer is preferably 30 μm to 50 μm. Aluminum laminates, which are laminates of aluminum foil and polymers such as polyethylene or polypropylene, are particularly suitable.

[0059] The nonaqueous electrolyte secondary battery of the embodiment may be in various forms such as a coin-type battery, a laminate-type battery, and a wound-type battery.

[0060] Example

[0061] The embodiments of the present invention have been described above. The following describes examples of the present invention. The embodiments and examples described below are merely illustrative of the present invention and are not intended to limit the technical scope of the present invention to the specific embodiments or specific examples.

[0062] (Fabrication of Positive Electrode, All Examples and Comparative Examples)

[0063] As the positive electrode active material, Li (Ni 0.9 Co 0.05 Mn 0.05)O2 (97.5% by mass), polyvinylidene fluoride (PVDF, 1.5% by mass) as a positive electrode binder, and carbon nanotubes (multi-walled carbon nanotubes (MWCNT, 1% by mass) as a conductive additive are mixed to form a positive electrode active material mixture. The positive electrode active material mixture is dispersed in N-methyl-2-pyrrolidone to prepare a positive electrode slurry. The positive electrode slurry is uniformly coated on a single surface of an aluminum current collector with a thickness of 12 μm. The thickness of the coating film is adjusted so that the initial charge capacity per unit area is 4.0 mAh / cm 2 After drying, the positive electrode active material layer was compressed using a roller press to a density of 3.5 g / cm 3 The positive electrode is produced by adjusting the method.

[0064] (Fabrication of Negative Electrode, Example 1)

[0065] As the negative electrode active material, SiO is used as a silicon-based active material (A). x (x=1.0, D 10 =11.0 μm, D 90 = 19.2 μm), artificial graphite (D) as a carbon-based active material (B) containing secondary particles formed by aggregation of primary particles 10 =7.9 μm, D 90 = 21.4 μm), and artificial graphite (D) as a carbon-based active material (C) including primary particles that do not aggregate with each other and form secondary particles. 10 =4.8 μm, D 90 =17.5 μm). The negative electrode active material mass ratio (SiO x , the mass ratio of artificial graphite to the carbon-based active material (B) of the negative electrode and the carbon-based active material (C) of the negative electrode (expressed as (A) / [(B)+(C)] in the table)) is set to 85 / 15, and the mass ratio of the carbon-based active material (B) to the carbon-based active material (C) is set to 1 / 1 to prepare a negative electrode active material mixture. The active material mixture (96.6% by mass), a polyacrylic acid-based binder (trade name: 10CLPAH, Fujifilm Wako Pure Chemical Industries, Ltd., 3.0% by mass) as a negative electrode binder, single-walled carbon nanotubes (SWCNT, 0.3% by mass) as a conductive additive, and carboxymethyl cellulose (CMC, 0.1% by mass) are dissolved and dispersed in an aqueous solvent to prepare a negative electrode slurry. The negative electrode slurry is evenly coated on a Cu current collector with a thickness of 8 μm. The thickness of the coating film is adjusted so that the initial charge capacity per unit area is 4.3 mAh / cm 2Then, compression molding was performed using a roller press to obtain a negative electrode active material layer with a density of 1.65 g / cm 3 The negative electrode is produced by adjusting the method.

[0066] In addition, SiO used in the examples x Suitable SiO can be obtained from, for example, Sigma-Aldrich, Kojun Chemical Research Institute Co., Ltd., Kanto Chemical Co., Ltd., Fujifilm Wako Pure Chemical Industries, Ltd., and the like. x The surface coating composition, surface conditions such as roughness, and particle size can be adjusted by using them alone or in combination, and using known methods such as heat treatment such as firing, chemical treatment such as chemical vapor deposition (CVD), mechanical treatment such as crushing and classification, and sputtering. In addition, suitable graphite can be obtained from Nippon Graphite Industries, Ltd., Resonac Co., Ltd., and the like. The surface coating composition, surface conditions such as roughness, and particle size can be adjusted by using them alone or in combination, and using known methods such as heat treatment such as firing, chemical treatment such as CVD, mechanical treatment such as crushing and classification, and sputtering.

[0067] The conductive additive used here is a collection of SWCNTs, formed by agglomerating to form a longer, more elongated shape than a single SWCNT. Multiple SWCNTs are arranged on the surface of the negative electrode active material, contacting any two or more of the silicon-based active material (A), the carbon-based active material (B), and the carbon-based active material (C). Such SWCNTs can be obtained from, for example, Meijo Nano Co., Ltd., Honjo Chemical Co., Ltd., and Kusumoto Chemical Co., Ltd.

[0068] In other examples and comparative examples, the type of negative electrode active material used and the amount of the negative electrode active material blended were changed as shown in Table 1. Silicon-based active material (A) SiO x The carbon-based active material (B), carbon-based active material (C), and conductive additive were obtained from the same sources as in Example 1. The mass ratio of carbon-based active material (B) to carbon-based active material (C) was set at 7:3 for Example 6 and 1:1 for the other Examples and Comparative Examples, as in Example 1. The negative electrode active material layer was prepared using the same method as in Example 1 in all Examples and Comparative Examples. In the table, % indicates the ratio relative to the total solid mass of the negative electrode active material.

[0069] (Fabrication of Lithium-Ion Secondary Batteries, All Examples and Comparative Examples)

[0070] The positive electrode and negative electrode were cut into 3 cm × 3 cm pieces and placed facing each other with a separator interposed therebetween. The separator used was a 10 μm thick microporous polyethylene film coated with ceramic on both sides.

[0071] The non-aqueous electrolyte is prepared by mixing an organic solvent with a supporting salt. The volume ratio of cyclic carbonate (EC) to chain carbonate (DEC, EMC) is adjusted to 1 / 6, and lithium hexafluorophosphate (LiPF6) and fluoroethylene carbonate (FEC) are added as supporting salts.

[0072] The positive electrode, negative electrode, separator, and non-aqueous electrolyte described above are placed in a laminated outer package, and the laminate is sealed to produce a lithium-ion secondary battery serving as a non-aqueous electrolyte secondary battery. The positive and negative electrodes are electrically connected from the outside of the laminate via tabs.

[0073] (Evaluation of lithium-ion secondary batteries)

[0074] The capacity retention rate and the decrease in average voltage during 1 C discharge of the lithium ion secondary batteries produced in each of the Examples and Comparative Examples were measured and evaluated by the following methods.

[0075] (Energy density)

[0076] The produced battery was charged at 7.2 mA, and after the upper limit voltage reached 4.2 V, it was charged at a constant voltage until the total charging time reached 12 hours. Then, it was discharged at a constant current of 7.2 mA until the lower limit voltage reached 2.5 V. After charging again under the same conditions, it was placed in a constant temperature chamber at 45°C for 3 days, and discharged again under the same conditions, and then charged and discharged again. The capacity and average voltage at the final discharge were evaluated. In addition, after the evaluation was completed, the thickness of the laminated battery (hereinafter sometimes referred to as "battery cell") was evaluated.

[0077] Based on the thickness of the battery cell, calculate the sum of the thickness of the positive electrode active material layer, half the thickness of the positive electrode current collector, the thickness of the separator, the thickness of the negative electrode active material layer, and half the thickness of the negative electrode current collector, which are the unit cell components of the laminated battery. Specifically, subtract the thickness of the laminate, half the thickness of the positive electrode current collector, and half the thickness of the negative electrode current collector from the thickness of the battery cell.

[0078] According to the following calculation formula:

[0079] [Number 1]

[0080] (Capacity of the cell during discharge) × (Average voltage of the cell during discharge) / (Area of ​​the electrode) / (Thickness of the positive electrode active material layer + Half the thickness of the positive electrode current collector + Thickness of the separator + Thickness of the negative electrode active material layer + Half the thickness of the negative electrode current collector)

[0081] The energy density of the unit cell components of the laminated battery was determined.

[0082] (Capacity maintenance rate)

[0083] The fabricated battery was placed in a thermostatic chamber at 45°C and charged at 30 mA. After the upper limit voltage reached 4.2 V, the battery was charged at a constant voltage until the total charging time reached 2.5 hours. The battery was then discharged at a constant current of 30 mA until the lower limit voltage reached 2.5 V. This charge and discharge cycle was repeated 100 times, and the ratio of the discharge capacity at the 100th cycle to the discharge capacity at the first cycle was taken as the capacity retention rate after 300 cycles.

[0084] The following table shows the results of Comparative Examples and Examples.

[0085] [Table 1]

[0086]

[0087] [Table 2]

[0088]

[0089] The non-aqueous electrolyte secondary battery using the negative electrode for non-aqueous electrolyte secondary batteries of the embodiment of the present invention has high energy density and high capacity retention rate after charge and discharge. On the other hand, with respect to the non-aqueous electrolyte secondary battery using the negative electrode for non-aqueous electrolyte secondary batteries of the comparative example, it was confirmed that either the energy density or the capacity retention rate was reduced, and it was impossible to improve both the energy density and the lifespan at the same time. By adjusting the mixing ratio of the silicon-based active material and the graphite-based active material and removing the SiO and the two graphite particles, the cumulative particle size distribution D10 is optimized, and an appropriate particle filling density of the negative electrode active material layer can be obtained, and the expansion of the electrode can be suppressed, thereby improving the energy density or the cycle capacity retention rate of the non-aqueous electrolyte secondary battery. Furthermore, the D of D90 is adjusted to max With D90 min The ratio of D90 is D max / D90 min Setting it to 2 or less is more effective.

[0090] The negative electrode for the nonaqueous electrolyte secondary battery of the present invention has been described in detail above, but the present invention is not limited to the above embodiments and examples, and various improvements and modifications can be made without departing from the spirit of the present invention.

Claims

1. A negative electrode for a non-aqueous electrolyte secondary battery, characterized in that: The negative electrode includes a negative electrode active material layer containing a negative electrode active material, a binder and a conductive additive. The negative electrode active material includes: a silicon-based active material (A) containing SiO x (where x is a number that satisfies 0.5≦x≦1.6); A carbon-based active material (B) comprising secondary particles formed by agglomeration of primary particles; and The carbon-based active material (C) includes primary particles that do not form secondary particles, In the volume-based cumulative particle size distribution of the negative electrode active material particles, the particle size at which the cumulative particle volume from the smaller particle size reaches x [%] of the total particle volume is expressed as Dx [μm], D10 of the silicon-based active material (A) A 3 μm or more, When the silicon-based active material (A) is added to D10 A 、D10 of the carbon-based active material (B) B , and D10 of the carbon-based active material (C) C The largest value of D10 is set as D10 max , set the minimum value to D10 min When D10 max / D10 min The value is below 2.5, When the silicon-based active material (A) is A 、D90 of the carbon-based active material (B) B , and D90 of the carbon-based active material (C) C The largest D90 value among the values ​​is set as D90 max , set the minimum value to D90 min When D90 max / D90 min The value is 2.0 or less.

2. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein D50 of the silicon-based active material (A) A It is 7 μm or more and 13 μm.

3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein The carbon-based active material (B) and the carbon-based active material (C) include artificial graphite, hard carbon, soft carbon, or any mixture thereof.

4. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein The carbon-based active material (B) is artificial graphite whose surface is coated with amorphous carbon, and the carbon-based active material (C) is artificial graphite whose surface is not coated.

5. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein The content of the silicon-based active material is 10 mass % or more and 20 mass % or less relative to the total amount of the silicon-based active material (A), the carbon-based active material (B), and the carbon-based active material (C) in the negative electrode.

6. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein The conductive additive includes carbon nanotubes.

7. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 6, wherein The conductive additive is a collection of single-walled carbon nanotubes.

8. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 7, wherein A portion of the conductive additive is present in a state of being previously attached to at least one surface of the silicon-based active material (A), the carbon-based active material (B), and the carbon-based active material (C).

9. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 8, wherein The adhesive comprises polyacrylic acid. 10 . A non-aqueous electrolyte secondary battery comprising at least the negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 , a positive electrode for a non-aqueous electrolyte secondary battery, a separator, and an electrolyte.